Determination of competencies of instructor B and trainer A in ski - Deliens, T.; Zinzen, E.; Huts, K. (Abstractbook. The First International Low Lands Congress on Science and Skiing, Brussels, October 11th, 2008)
The primary research question of this study was to determine what competencies an instructor B and a trainer A ski have to posses by questioning ski-experts. In addition it is the purpose, in the nearby future, to implement the found competencies in the courses of the Flemish training school.